Retinopathy in adults with hypertension and diabetes mellitus in Western Tanzania: a cross‐sectional study. Issue 10 (3rd August 2020) - Woodward, Richmond; Mgaya, Evarista; Mwanansao, Christopher; Peck, Robert N.; Wu, Alan; Sun, Grace
Abstract: Objective: Little is known about the retinal manifestations of arterial hypertension (HTN) and diabetes mellitus (DM) in Western Tanzania and how to maximise the utilisation of scarce eye health resources. To address this, we determined the prevalence of hypertensive and diabetic retinopathy (DR), associated risk factors and relevant patient knowledge. Methods: Adults with HTN or DM attending outpatient clinics at Bugando Medical Center (BMC) from June to August 2017 were enrolled. Fundus photographs were obtained, and data were collected on blood pressure (BP), body mass index (BMI), blood sugar, visual acuity (VA) and responses to questions about the effects of HTN and DM on the eye. Results: A total of 180 persons were screened. When only individuals with DR were considered, bivariate regression found systolic BP was significantly associated with severity of DR ( P  = 0.034). Receiver operating characteristic (ROC) curve analysis using the maximum Youden index revealed the optimum cut‐off using duration of DM to predict any DR was 8 years (AUC = 0.75, 95% CI 0.65–0.85). Fewer persons with HTN were aware of the effect of high BP on the eye (61.6%) than persons with DM who were aware of the effect of high blood sugar on the eye (74.4%) ( P  = 0.048). Conclusion: Efforts should be made to vigorously treat HTN among adults with DM and refer adults with duration of DM of 8 years or more for a dilated retinal examination. Additional efforts should be made to promote awareness of the sight threatening potential of HTN in resource‐limited settings. Abstract : Objectif: On en sait peu sur les manifestations rétiniennes de l'hypertension artérielle (HTA) et du diabète sucré (DS) dans l'ouest de la Tanzanie et sur la manière de maximiser l'utilisation des rares ressources de la santé oculaire. Pour répondre à ceci, nous avons déterminé la prévalence de la rétinopathie hypertensive et diabétique (RD), les facteurs de risque associés et la connaissance du patient concerné. Méthodes: Les adultes atteints d'HTA ou de DS fréquentant les cliniques ambulatoires au Bugando Medical Center (BMC) de juin à août 2017 ont été inscrits. Des photos du fond de l'œil ont été obtenues et des données ont été recueillies sur la pression artérielle (TA), l'indice de masse corporelle (IMC), la glycémie, l'acuité visuelle (AV) et les réponses aux questions sur les effets de l'HTA et du DS sur l'œil. Résultats: Au total, 180 personnes ont été dépistées. Lorsque seules les personnes atteintes de RD étaient considérées, la régression bivariée a révélé que la TA systolique était significativement associée à la sévérité de la RD ( P  = 0, 034). L'analyse de la courbe des caractéristiques de fonctionnement du récepteur (ROC) à l'aide de l'indice de Youden maximal a révélé que le seuil optimal utilisant la durée du DS pour prédire toute RD était de 8 ans (ASC = 0, 75 ; IC95%: 0, 65 à 0, 85). Moins de personnes atteintes de HTA étaient conscientes de l'effet d'une TA élevée sur l'œil (61, 6%) que les personnes atteintes de DS qui étaient conscientes de l'effet de l'hyperglycémie sur l'œil (74, 4%) ( P  = 0, 048). Conclusion: Des efforts doivent être faits pour traiter effectivement l'HTA chez les adultes atteints de DS et référer les adultes avec une durée de DS de 8 ans ou plus pour un examen de la rétine dilatée. Des efforts supplémentaires devraient être faits pour promouvoir la prise de conscience du potentiel de menace pour la vue de l'HTA dans les zones à ressources limitées.